Is phenalenyl aromatic? - Dias, Jerry Ray (Array, 2020)
The rings phenalenyl are determined using some quantitative aromatic indices to have around 40 % the aromaticity of benzene. The monocation, monoanion, and monoradical of phenalenyl are found to be equally aromatic.